Molecular characterization of Encarsia inaron (Walker, 1839) naturally associated with Bemisia tabaci (Gennadius, 1889) in Brazil - Cirino, Thaís Carolina Silva [UNESP]; Alvarez, Daniel de Lima [UNESP]; Costa, Valmir Antonio; Müller, Cristiane; Watanabe Maranho, Luís Fernando [UNESP]; De Marchi, Bruno Rossitto [UNESP]; Bello, Vinicius Henrique [UNESP]; Sakate, Renate Krause [UNESP]; de Oliveira, Regiane Cristina [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2022)
This work is the first record of Encarsia inaron (Walker, 1839) (Hymenoptera: Aphelinidae) parasitizing Bemisia tabaci (Gennadius, 1889) (Hemiptera: Aleyrodidae) on soybeans in Brazil. Morphological and molecular characterizations are provided, in addition to verification of the presence of E. inaron in areas infested by whiteflies, indicating that the wasp can potentially be used in integrated management programs. Additionally to morphological verification, the molecular analysis allowed the identification of some degree of genetic variability in the genome of the parasitoid.
Caracterización molecular de Encarsia inaron (Walker, 1839) asociada naturalmente con Bemisia tabaci (Gennadius, 1889) en Brasil
Keywords: biological control; integrated pest management; natural enemy; parasitoid; whiteflies